Gadolinium-conjugated star-block copolymer polylysine-modified polyethylenimine as high-performance T1 MR imaging blood pool contrast agents. Issue 9 (30th January 2018) - Huang, Zhongjie; Chen, Yicun; Liu, Daojun; Lu, Chao; Shen, Zhiwei; Zhong, Shuping; Shi, Ganggang
Abstract : Core–shell copolymers have received widespread attention because of their unique properties, such as suitable for surface modification and increasing the functionality. Abstract : Core–shell copolymers have received widespread attention because of their unique properties, such as suitable for surface modification and increasing the functionality. Thus, they have been increasingly used in many fields including biomedical, pharmaceutical, electronics and optics. Here, a new core–shell copolymer system was developed to synthesize potential blood pool contrast agent (CA) for magnetic resonance imaging (MRI). The novel CA with high T 1 relaxivity was synthesized by conjugating gadolinium (Gd) chelators onto star-block copolymer polyethylenimine-grafted poly(l -lysine) (PEI–PLL) nanoparticles (NPs). The T 1 relaxivity of PEI–PLL–DTPA–Gd NPs measured on a 7.0 T small animal MRI scanner was 8.289 mM −1 s −1, higher than that of T 1 contrast agents widely used in the clinic, such as Gd–DTPA (also known as Magnevist, r 1 = 4.273 mM −1 s −1 ). These results show that PEI–PLL–DTPA–Gd exhibits more efficient T 1 MR contrast enhancement compared to Gd–DTPA. More importantly, the PEI–PLL–DTPA–Gd core–shell NPs exhibited extremely low toxicity when measured against the HepG2 cell line over a similar concentration rang of Magnevist. In in vivo experiments, PEI–PLL–DTPA–Gd not only displayed good T 1 contrast enhancement for the abdominal aorta, but also showed prolonged blood circulation time compared with Gd–DTPA, which should enable longer acquisition time, for MR and MR angiographic images, with high resolution in clinical practice. PEI–PLL–DTPA–Gd NPs have potential to serve as high T 1 relaxivity blood pool MRI CA in the clinic.